APPLICATION OF UNCERTAIN MAX PLUS LINEAR FOR SHIP SCHEDULE SAFETY ANALYSIS: A CASE STUDY OF KM. LAMBELU - Nurul Fuady Adhalia H; Mardhiyyah Rafrin; Aditya Putra Pratama; Rifaldy Atlant Tungga; Bayu Bayu; Syahrul Ramadhan Tahir (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
This study aims to analyze the safety of the KM. Lambelu passenger ship schedule on its Parepare-Balikpapan route using the uncertain Max-Plus Linear (uMPL) approach. The uMPL model is used to represent the dynamics by considering the uncertainty of travel times between ports. Forward reachability analysis is conducted to verify whether the ship scheduling system meets the established safety criteria. The analysis results show that the analysis indicates that the KM. Lambelu scheduling system has safety vulnerabilities. This finding indicates the presence of potential accident or incident risks and emphasizes the need for evaluation and improvement of scheduling system to ensure ship operation within safe limits. This study identifies potential problems and risks associated with these findings and provides recommendations for improving the ship schedule.